An Analysis of Pumped Thermal Energy Storage With De-coupled Thermal Stores - Davenne, Tristan R.; Peters, Benjamin M. (Frontiers in Energy Research, 2020)
Results from the first demonstration of Pumped Thermal Energy Storage (PTES) were published in 2019, indicating an achieved turn-round efficiency of 60–65% for a system capable of storing 600 kWh of electricity. PTES uses a theoretically reversible thermodynamic cycle involving compression and expansion stages with constant pressure heat addition and rejection to hot and cold thermal stores. Energy storage turn-round efficiency largely depends on the isentropic efficiencies of the compression and expansion equipment, the thermal effectiveness of the thermal stores, the presence of circuit pressure drops, heat leaks to and from the system and electrical machine efficiencies. We present a simulation model of a PTES system which is used to produce an inventory of the relative magnitudes of the various system losses. We consider the feasibility of a large-scale, 1 GWh nominal storage capacity, PTES system with de-coupled thermal stores; and provide comparison with the so far more investigated, coupled system. Based on ambitious yet realistic component performances, we calculate an energy storage turn around efficiency of 65.3 and 59.5% for the coupled and de-coupled systems, respectively. Even with dwell times in the charged state as long as 5 days, a turn-round efficiency of over 50% is still predicted in both systems; suggesting that PTES could offer a viable large-scale, long duration energy store.